1988
DOI: 10.1111/j.1095-8649.1988.tb05507.x
|View full text |Cite
|
Sign up to set email alerts
|

Diel feeding periodicity, daily ration and prey selection of a riverine population of juvenile chinook salmon, Oncorhynchus tshawytscha (Walbaum)

Abstract: The diel feeding periodicity, daily ration and prey selection of juvenile chinook salmon, Oncorhynchus uhawyrscha, were studied in relation to the available prey. Maximum dry weight of food intake occurred about dawn, when mayflies were the major prey, but the greatest number of freshly eaten prey occurred during the afternoon, when chironomids and terrestrial dipterans predominated. Feeding activity at night was low, with smaller mayflies comprising up to 50% of the prey. During the day the young salmon fed s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
65
2

Year Published

1989
1989
2018
2018

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 66 publications
(74 citation statements)
references
References 22 publications
7
65
2
Order By: Relevance
“…One of the few reports is by Newman & Waters (1984), who reported that stream salmonids ate a considerable number of small aphids (< 3 mm body size) in the drift, though they also consumed the larger animals of their preferred prey, Gammarus psuedolimnaeus, at night in a small Minnesota stream. On the other hand, Sagar & Glova (1988) found that the drift-feeding fry of Chinook salmon Oncorhynchus tshawytscha took little advantage of the abundant drift of various sizes at night, presumably because of their limited vision at low light intensities. If Galaxias vulgaris has similar sight limitations, then benthic feeding would be easier at low light levels in which other sensory stimuli (e.g., smell, touch) may be important for locating prey.…”
Section: Discussionmentioning
confidence: 99%
“…One of the few reports is by Newman & Waters (1984), who reported that stream salmonids ate a considerable number of small aphids (< 3 mm body size) in the drift, though they also consumed the larger animals of their preferred prey, Gammarus psuedolimnaeus, at night in a small Minnesota stream. On the other hand, Sagar & Glova (1988) found that the drift-feeding fry of Chinook salmon Oncorhynchus tshawytscha took little advantage of the abundant drift of various sizes at night, presumably because of their limited vision at low light intensities. If Galaxias vulgaris has similar sight limitations, then benthic feeding would be easier at low light levels in which other sensory stimuli (e.g., smell, touch) may be important for locating prey.…”
Section: Discussionmentioning
confidence: 99%
“…This reduction in foraging capability is offset for part of the year by a greater availability of food, since in general both the total quantity of drift and the average size of the prey species increases at night (e.g. Elliott 1965Elliott , 1967Elliott , 1970Elliott , 1973Sagar & Glova 1988). From spring until autumn, when stream salmonids are active (and potentially able to feed) throughout the diel cycle, most studies of wild fish have found peaks in feeding at dawn and/or dusk (when light intensities are not constraining and drift abundance is higher than the daytime level) but rather little and less selective foraging during the night itself (Elliott 1970(Elliott , 1973Jenkins, Feldmeth & Elliott 1970;Sagar & Glova 1988;Angradi & Griffith 1990;Riehle & Griffith 1993;Forrester, Chace & McCarthy 1994).…”
Section: Discussionmentioning
confidence: 99%
“…Leung et al (2009) used a simple bioenergetics approach to estimate drift consumption by young-of-the-year and 1-year-old cutthroat trout feeding in pools at 25% and 50% of their maximum daily consumption and concluded that 36%-71% of drift could be lost to fish predation in a small trout stream. While these estimates suggest predation on drift may be a large component of daytime drift depletion, foraging efficiency and activity are generally much lower at night (Allan 1978;Sagar and Glova 1988; but see Elliott 2011) when drift abundances generally peak in fish-bearing streams (Bishop 1969). Therefore, while fish may deplete a major portion of diurnal drift in smaller streams, overall losses due to predation may be a negligible fraction of the total drift flux.…”
Section: Drift Exitmentioning
confidence: 99%